Employability: a contemporary review for higher education stakeholders. (2nd January 2018) - Small, Lynlea; Shacklock, Kate; Marchant, Teresa
Abstract: Higher education institutions are under pressure to produce employable graduates who are required to contribute to the sustainability of strong economic growth and development. As such, the onus is on the higher education sector to present graduates to the labour market who are both work ready and have attained employability. This article contributes to the discussion surrounding the employability of graduates by: enhancing understanding and discussing contemporary evidence and debate around employability; showing the genesis, influence and synthesis of the major models associated with employability; summarising the boundaries and barriers to graduate employment; and exploring the determinants of employability from the employer's perspective. Importantly, the article summarises the contemporary theoretical bases of employability in the one place. Recommendations are made regarding further research and the need for further theoretical contributions.